Organizing Experimental And Pilot Studies Based On Foreign Experiences In Geographical Sciences - S.T. Abdurahmanov; R. T. Gaypova; M.M. Sapayeva (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the theoretical and practical aspects of organizing experimental and pilot studies in the teaching of geography based on foreign experiences. It also examines the possibilities of adapting advanced teaching methods from developed countries to the Uzbek education system.